Impact of Entrepreneurial and Environmental Sustainability Orientation on Organizational Performance in Kathmandu Valley - Shrestha, Roshni; Ghimire, Samita; Tuladhar, Jibitesh Manandhar; Karmacharya, Rakshya; Thapa, Yubisha; Thakur, Ritesh Kumar (Apex Journal of Business and Management, 2025)
This research investigates the mediating effect of Environmental Sustainability Orientation (ESO) on the relationship between Entrepreneurial Orientation (EO) and Organizational Performance (OP) within the Kathmandu Valley. The study aims to determine how an organization’s sustainability knowledge, commitment, and practices mediate the positive impacts of innovations, proactiveness, and risk-taking on organizational performance. A quantitative approach was employed, collecting data from 64 firms in Kathmandu using a standardized questionnaire. Statistical analyses, including regression and correlation analysis, were conducted to examine the relationships between the variables. The results indicate that EO positively influences organizational performance. Additionally, ESO serves as a significant mediating factor between EO and OP, highlighting the synergistic benefits of integrating entrepreneurial and sustainability practices. The findings suggest that organizations experience enhanced performance when entrepreneurship is aligned with sustainability efforts. The study emphasizes the importance of fostering both entrepreneurial orientation and environmental sustainability within organizations to optimize performance outcomes. Practitioners are encouraged to develop strategies that integrate these orientations to achieve better organizational results.